The Effect of the Cooperative Learning Model: Student Teams Achievement Division (STAD) on Science Learning Outcomes of Fourth Grade Students at SD Negeri 01 Tiumang - Saputra, Agus; Asmara, Dwi Novri; Astarina, Lusia (TOFEDU: The Future of Education Journal, 2025)
This study is motivated by the low learning outcomes of Science (IPAS) students. Therefore, this research aims to examine the effect of implementing the Cooperative Learning Model: Student Teams Achievement Division (STAD) assisted by Question Ball media on Science learning outcomes for fourth-grade students at SD Negeri 01 Tiumang. This research employs a quantitative approach with a quasi-experimental design using a one-group pretest-posttest design. The population of this study consisted of all fourth-grade students at SD Negeri 01 Tiumang, with a saturated sampling technique used to select the sample. Data collection was done using a test with a set of questions as the instrument. After applying the Cooperative Learning Model: Student Teams Achievement Division (STAD), the average pretest score was 56, and the posttest score was 72, indicating an improvement in posttest scores. Based on the analysis using non-parametric tests, the asymptotic significance (2-tailed) value was 0.000, which is smaller than 0.05, thus the hypothesis is accepted. This indicates that there is a significant difference between the pretest and posttest results. Therefore, it can be concluded that the implementation of the Cooperative Learning Model: Student Teams Achievement Division (STAD) with Question Ball media has a positive effect on Science learning outcomes for fourth-grade students at SDN 01 Tiumang.